Delineation of pona complex of yam in Ghana using SSR markers - Otoo, E.; Akromah, R.; Kolesnikova-Allen, M.; Asiedu, Robert (2009)
Yam (Dioscorea spp), a multi-species, polyploid, and vegetatively propagated tuber crop, is cultivated widely in the tropics and subtropics. Over 95% of the world's yam production occurs in West and Central Africa where white yam (Dioscorea rotundata Poir.) is the most important among cultivated species. The most popular landrace cultivar of yams on the market in Ghana is called 'Pona'. Yam sellers often pass off any yam of good culinary characteristics as 'Pona' and consumers are at a loss as to the genuine properties of the cultivar. Data from field characterization of several accessions suggest a cultivar group with significant morphological diversity. To determine the population structure of this yam group and the true genetic identity of 'Pona', an investigation was conducted on molecular variability and relationships among 72 accessions of D. rotundata collected throughout Ghana. The experimental set included accessions classified as true 'Pona' by experienced yam farmers as well as other varieties of yams available from local markets. The materials were screened with 21 microsatellite (SSR) markers available for yams. 13 (62%) of them were found to be polymorphic and used for genotyping of the full experimental set. Two-dimensional scatter diagram of the 1 st and 2 nd principal coordinates showed a wide dispersion among the accessions. To determine the similarity and relationships among the studied individuals, a neighbour-joining tree was constructed based on the shared allele distance (DAS) between individuals using Darwin, v. 5.0.153. Cluster analysis performed by Darwin v. 5.1.153, using unweighted the neighbour-joining method clearly separated the accessions into four main groupings: True Pona, Larebako, Muchumudu and Dente. The findings of this study prove the ability of microsatellite molecular markers to separate closely related groups within species due to their high specificity. The next steps in identifying the unique characteristics of Pona are discussed.